Evaluation of acute cardiac and chest wall damage after shocks with a subcutaneous implantable cardioverter-defibrillator in swine - KILLINGSWORTH, CHERYL R. (2013)
BACKGROUND: A subcutaneous implantable cardioverter defibrillator (S-ICD) could ease placement and reduce complications of transvenous ICDs, but requires more energy than transvenous ICDs. Therefore we assessed cardiac and chest wall damage caused by the maximum energy shocks delivered by both types of clinical devices. METHODS: During sinus rhythm, anesthetized pigs (38±6 kg) received an S-ICD (n = 4) and five 80-Joule (J) shocks, or a transvenous ICD (control, n = 4) and five 35-J shocks. An inactive S-ICD electrode was implanted into the same control pigs to study implant trauma. All animals survived 24-hours. Troponin I and creatine kinase muscle isoenzyme (CK-MM) were measured as indicators of myocardial and skeletal muscle injury. Histopathological injury of heart, lungs, and chest wall was assessed using semi-quantitative scoring. RESULTS: Troponin I was significantly elevated at 4- and 24-hours (22.6±16.3 and 3.1±1.3 ng/ml; baseline 0.07±0.09 ng/ml) in control pigs but not in S-ICD pigs (0.12±0.11 and 0.13±0.13 ng/ml; baseline 0.06±0.03 ng/ml). CK-MM was significantly elevated in S-ICD pigs after shocks (6544±1496 and 9705±6240 U/L; baseline 704±398 U/L) but not in controls. ECG changes occurred post-shock in controls but not in S-ICD pigs. The myocardium and lungs were histologically normal in both groups. Subcutaneous injury was greater in S-ICD compared to controls. CONCLUSION: Although CK-MM suggested more skeletal muscle injury in S-ICD pigs, significant cardiac, lung, and chest wall histopathological changes were not detected in either group. Troponin I data indicate significantly less cardiac injury from 80-J S-ICD shocks than 35-J transvenous shocks.